Integrating 21st century elements to enhance communication skills in TVET: A brief perspectives towards evaluation studies - Jaswant Singh, Hardev Singh Sokhal; Abdullah Adnan, Mohamed; Nik Aloesnita, Nik Mohd Alwi (Penerbit UMPSA, 2025)
In order to meet the changing demands of the contemporary workforce, technical and vocational education must undergo adaptation (UNESCO, 2020). The ability to effectively communicate, including digital literacy, collaboration, and interpersonal skills, is vital for success in diverse professional environments. This concept paper aims to provide a framework for incorporating 21st-century elements into the training of communication skills in TVET, utilizing the evaluation model for comprehensive evaluation.